Information asymmetry and corporate governance mechanisms among UAE listed companies - Bajrei, Saleh Salem Saeed; Lode, Nor Asma (2014)
This study uses the agency theory to systematically investigate the relationship between corporate governance mechanisms (i.e. board size, board independence, duality, board meetings, director’s ownership, and audit committee size) and the level of information asymmetry in UAE.The multiple regression analysis provides evidence that board size is positively related to information asymmetry, while, board independence, board meetings, directors’ ownership and audit committee size are negatively related to information asymmetry.The findings show that the information asymmetry among the United Arab Emirates (UAE) companies is high and the implementation of the Code of Corporate Governance is more likely to be underdevelopment.